2009
DOI: 10.1177/1362361307098511
|View full text |Cite
|
Sign up to set email alerts
|

`Hath charms to soothe . . .'

Abstract: A B S T R A C TSemi-structured interviews were conducted with 12 highfunctioning adults on the autism spectrum, in order to examine the nature of their personal experiences of music. Consistent with the literature on typically developing people's engagement with music, the analysis showed that most participants exploit music for a wide range of purposes in the cognitive, emotional and social domains, including mood management, personal development and social inclusion. However, in contrast to typically develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 35 publications
4
34
2
Order By: Relevance
“…However, they may listen to music to satisfy emotional needs. Allen, Hill, and Heaton (2009) found that adults with ASD listen to music to alter or induce states of arousal. Further, there exists evidence that the ability to categorize musical emotions is preserved in ASD.…”
Section: Perception Of Emotion In Musicmentioning
confidence: 98%
“…However, they may listen to music to satisfy emotional needs. Allen, Hill, and Heaton (2009) found that adults with ASD listen to music to alter or induce states of arousal. Further, there exists evidence that the ability to categorize musical emotions is preserved in ASD.…”
Section: Perception Of Emotion In Musicmentioning
confidence: 98%
“…In addition, different questions can be asked of participants in future studies such as how music makes them feel, how it makes someone else feel, which music they prefer, etc. Interviews on experiences with music performed by Allen et al (2009) with adults with ASD could be adapted to adolescents in pursuit of these questions.…”
Section: Intensity and Confidence Ratings And Response Timesmentioning
confidence: 99%
“…Compared to controls, children and adolescents with ASD are equally distracted by music when it accompanies moving visual images (Bhatara et al 2009). Adults with ASD respond to and appreciate music in a fashion similar to the typical listener, as indicated by a semi-structured interview (Allen et al 2009). However, adults with ASD tend to describe the effects of music in terms of arousal or internally focused language (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, music serves important intrapersonal functions (Patel 2008). As one adult autistic participant in the study carried out by Allen et al (2009) said, 'I find that sometimes if you're feeling very sad or something, listening to that kind of music can put you in touch with your feelings, it can help you to access your feelings. You can really feel the feelings instead of their just being there, you can really dwell in that state and deal with it.'…”
Section: Future Directionsmentioning
confidence: 99%
“…So, while a clear global bias was observed when stimuli were presented at a moderate tempo, this was lost and responses became random when stimuli were presented slowly. It was interesting that in a recent study carried out with high-functioning adults with ASD (Allen et al 2009), 2 of the 12 participants in the study expressed a dislike for slow music, describing it as 'dirgey' and 'dirge-like'. This suggests that for a subgroup of individuals, temporal processing abnormalities result in a degree of musical impairment.…”
Section: Spared Music Perception In Non-savant Children With Autismmentioning
confidence: 99%